2009
DOI: 10.1007/978-1-60327-389-3_25
|View full text |Cite
|
Sign up to set email alerts
|

Rat Genomics Applied to Psychiatric Research

Abstract: Psychiatric diseases are very debilitating and some of them highly prevalent (e.g., depression or anxiety). The rat remains one model of choice in this discipline to investigate the neural mechanisms underlying normal and pathological traits. Genomic tools are now applied to identify genes involved in psychiatric illnesses and also to provide new biomarkers for diagnostic and prognosis, new targets for treatment and more generally to better understand the functioning of the brain. In this report, we will revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 87 publications
0
3
0
Order By: Relevance
“…In this sense, the overlap between these behaviors will depend on the genetic background of each population studied and are expected to be mostly partial only (see below). For detailed review of genes related to animal models of anxiety see [55][56][57].…”
Section: The Linkage Of Emotional Traitsmentioning
confidence: 99%
“…In this sense, the overlap between these behaviors will depend on the genetic background of each population studied and are expected to be mostly partial only (see below). For detailed review of genes related to animal models of anxiety see [55][56][57].…”
Section: The Linkage Of Emotional Traitsmentioning
confidence: 99%
“…Regarding psychiatric-relevant phenotypes, Moisan and Ramos have listed over 160 QTLs that had been mapped in rats until 2010, including their names, chromosome positions, strains and statistical significance [ 44 ]. By analyzing currently available data from the RGD, we have identified 167 QTLs for emotionality-related traits, 82 for stress responses, 56 for anxiety and 64 for locomotor activity, some of which overlap with each other [ 12 ].…”
Section: Qtl Studies In Ratsmentioning
confidence: 99%
“…It has also helped to identify markers of disease and surrogate markers of drug response in chronic inflammation and age-related diseases (2,17,26). Recent studies, including some from our group, have also shown that M. tuberculosis-infected rats develop organized granulomas within the lungs while controlling the infection over time (32).…”
mentioning
confidence: 99%